Madness by Design: A Genealogy of an “Anti-Tradition” - Muhammad Ali Khalidi (European Journal of Analytic Philosophy)
Psychiatric conditions are commonly regarded as mental disorders or dysfunctions of the mind. Yet there is a wealth of historical theorizing about the mind that conceives of these conditions as, in some sense, a matter of design rather than dysfunction. This intellectual legacy is the topic of Justin Garson’s penetrating study, Madness: A Philosophical Exploration (2022). In this paper, I interpret Garson’s book as a genealogy (in the Foucauldian sense) of the “anti-tradition” that he labels “madness-as-design”. I argue that viewing the intellectual legacy that Garson analyzes through this genealogical lens has two benefits. First, it encourages us to identify other instances of madness-as-design (or madness-by-design), particularly those with an overtly political dimension, such as psychiatric conditions in a colonial context. Second, it should lead us to question the category of madness itself, which turns out to be radically disjointed, particularly since it cannot be unified under the rubric of disorder or dysfunction.